The Influence of Trust on Creativity: A Review - Chen, Yan; Yu, Cheng; Yuan, Yuan; Lu, Fang; Shen, Wangbing (Frontiers in Psychology, 2021)
Examining the trust-creativity relationship is important to promote creativity and organizational innovation. The goal of this study is to investigate how trust influences creativity by summarizing existing findings of diverse empirical studies. The impact of trust at different levels on creativity primarily manifests in three ways: (1) individuals' cognition- and affect-based trust has a positive effect on creativity together with the role of trust-derived perspective taking in creativity; (2) interpersonal trust helps enhance the joint creativity of an entire group via mediators such as team communication and commitment together with trust-evoked safety and the motivation to risk proposing, sharing, accepting or adopting uncommon ideas; (3) group trust has a positive, mostly indirect effect on creativity via mediating variables such as collaborative culture/climate and team communication. Potential implications and avenues for future research are also discussed.